PENGARUH CSR BIDANG SOSIAL EKONOMI DAN LINGKUNGAN TERHADAP KEBERDAYAAN MASYARAKAT (STUDI KASUS PT CIPTA AGUNG MANIS KABUPATEN KONAWE SELATAN) - Sofian Syarif; Iskandar Zainuddin Rela; Salahuddin Salahuddin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research aims to analyze the influence of corporate social responsibility in the social, economic and environmental fields on community empowerment. This research was carried out in Wunduwatu Village, Bumiraya Village and Mataiwoi Village, South Konawe Regency. Determining the location of this research was carried out purposively or deliberately. The respondents of this research are people who live around the company and have a plasma farming cooperative relationship with PT. Cipta Agung Manis, namely 90 people (proportional sampling). The variable for this research is CSR, covering the social, economic and environmental fields and community empowerment. The data analysis used in this research is descriptive quantitative analysis using class intervals and inferential quantitative analysis using SEM-PLS. The results of this research indicate that the implementation of CSR PT. Cipta Agung Manis is in the medium category. The company's CSR has been distributed well in society but still needs to be improved so that the implementation of the company's CSR can be very good or in the high category in terms of community empowerment. The empowerment of the community around the PT Cipta Agung Manis company is in the medium category. There is a significant influence between the implementation of PT Cipta Agung Manis' CSR on the community around the company.